Citalopram intoxication in four week old infant - Jo-Anne Janson; Arthur T. M. Wasylewicz; Marianne Eijkemans; Marieke Kerskes (BMC, 2020)
Abstract Background In contrast to intoxications in toddlers which can be due to accidental ingestions, many intoxications in infants are due to medication errors. To our knowledge, this is the first case report of a citalopram intoxication in an infant, and may offer new insight on possible screening methods for intoxication as well as pharmacokinetics of citalopram in small infants. Case presentation This case report describes an unintentional citalopram intoxication in a 4 week old infant due to a vitamin D drops 'look alike' error. The infant showed extreme jitteriness and opisthotonus at presentation, as well as prolonged signs of gastro-oesophageal reflux. No cardiac rhythm disturbances or convulsions were seen. The clinical course combined with Finnegan scores was correlated to and supported by pharmacokinetic and pharmacokinetic data of citalopram in the patient. Conclusions Using Finnegan scores in general pediatric practice could help objectify follow-up of acute intoxications in young infants with neurological symptoms.